When the Western is Weird. (Observations on a Certain Not Quite Traditional Genre and Three Not Quite Conventional Western Films) - Martin Boszorád (Slovenska Literatura, 2013)
The goal of the article is to reflect on a selected sample of the films which can be classified as westerns but they put the western mechanisms, conventions, clichés etc. into new unusual contexts. That way the limits of the original genre are exceeded, especially by means of the hybridization moment and the eclectic enhancement, most often by fusion with other genres. The text of the article is dedicated to the fragmentary analytical-interpretative reflection of resource materials which can be given an overall sub-genre or genre-hybrid tag „the weird western“. On the one hand, the concept of the study respects the interpretation of the equivalent English expression „weird western“ as the denomination of the genre combining the western mainly with the supernatural and science fiction elements, on the other hand, it carefully monitors the „weirdness“ as a result of the crossover of the western and genres different from science fiction (horror, musical and comedy etc.).